Prevalence, awareness, treatment and control of coexistence of diabetes and hypertension in Thai population - Siriwat Tiptaradol (2018)
Diabetes and hypertension are major independent risk factors for cardiovascular and renal diseases; however, prevalence and characteristics of the coexistence in general population is not clear. Data from Thai National Health Examination Survey III were used to estimate the prevalence of coexistence of diabetes and hypertension, and to estimate the proportion of awareness, treatment and control of both conditions. A total of 36,877 (male 17,614 and female 19,263) participants were included in the study. The prevalence of people with diabetes and hypertension was 3.2% (male 2.8% and female 3.6%). Approximately half of the diabetes patients (49.0%, 95%CI 45.6, 52.5) had hypertension, and 14.4% (95%CI 13.0, 16.0) of hypertensive patients had diabetes. After controlling for covariates, factors associated with coexistence of diabetes and hypertension included; age ≥60 years (adjust odds ratio 1.38, 95%CI 1.14, 1.73), having education less than 6 years (1.83, 95%CI 1.03, 3.38) and abdominal obesity (2.49, 95%CI 2.00, 3.10). More than 80% were unaware of having both conditions. Target for control of both glucose and blood pressure among those treated was achieved in only 6.2%. In conclusion, patients with diabetes or hypertension should be promoted to have weight control and screening for the comorbidity. © 2012 Siriwat Tiptaradol and Wichai Aekplakorn.